Pengembangan Media Game Edukasi Where is Myhometown Berbasis Android Materi Keragaman Budaya di Indonesia - Silviana Agustin; Novanita Whindi A (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The majority of children aged 9 years and over are very happy to play online games, thus making children lazy to open books to study. This study aims to develop an Android-based Where Is Myhometown Educational Game Media in Class IV Civic Education Lessons on Cultural Diversity in Indonesia. This research was carried out at SDN Cipinang Melayu 10 Pagi, in the even semester 2021/2022 academic year. This research has been tested by 3 validators, namely: media experts, material experts, and education experts. This media game has also been tested through a small group test containing 10 students and a large group test containing 20 students where the student is a fourth grade student at SDN Cipinang Melayu 10 Pagi. This study uses the Research and Development (R&D) method by applying the ADDIE model and the data collection technique is in the form of a questionnaire using a Likert scale. This educational game media where is myhometown succeeded in making it easy for students to understand the variety of Indonesian culture and its origins. By using this educational game, students become happier in learning Indonesian culture. Keywords: ADDIE, educational game